2015
DOI: 10.1073/pnas.1422858112
|View full text |Cite
|
Sign up to set email alerts
|

Caenorhabditis elegans microRNAs of the let-7 family act in innate immune response circuits and confer robust developmental timing against pathogen stress

Abstract: Animals maintain their developmental robustness against natural stresses through numerous regulatory mechanisms, including the posttranscriptional regulation of gene expression by microRNAs (miRNAs). Caenorhabditis elegans miRNAs of the let-7 family (let-7-Fam) function semiredundantly to confer robust stage specificity of cell fates in the hypodermal seam cell lineages. Here, we show reciprocal regulatory interactions between let-7-Fam miRNAs and the innate immune response pathway in C. elegans. Upon infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
81
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(86 citation statements)
references
References 60 publications
5
81
0
Order By: Relevance
“…[30-32] We selected miR targets, with low variability (i.e., miR-146b-5p) and high (i.e., miR-486-5p variability between samples, to validate measurement of expression by qPCR (Supplementary Table 1). We found similar magnitudes in fold-change for comparisons between insulin sensitive and insulin resistant individuals for miR-486-5p.…”
Section: Resultsmentioning
confidence: 99%
“…[30-32] We selected miR targets, with low variability (i.e., miR-146b-5p) and high (i.e., miR-486-5p variability between samples, to validate measurement of expression by qPCR (Supplementary Table 1). We found similar magnitudes in fold-change for comparisons between insulin sensitive and insulin resistant individuals for miR-486-5p.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, some evidence has demonstrated that miRNAs may play important roles in the regulation of innate immunity1718. In C. elegans , some specific miRNAs have been shown to be involved in the control of innate immune response to bacterial pathogens192021. However, the role of miRNAs in the control of the C. elegans innate immune response to C. albicans infection is still unclear.…”
mentioning
confidence: 99%
“…Taken together, these results revealed that appropriate regulation of miR-146b expression is critically important for fish to resist infection. However, several reported immune-related miRNAs were not differentially expressed in the three libraries, including let-7 family, miR-155 and miR-192 [58,59,60], probably due to species- or tissue-specific miRNA expression [7,10]. …”
Section: Discussionmentioning
confidence: 99%